Comorbidity in chronic obstructive pulmonary disease patient - Leonid I. Dvoretsky (LLC "MEDIAFORMAT", 2023)
The paper discusses the issue of comorbidity in patients with chronic obstructive pulmonary disease. The data on the prevalence of various comorbidities, clinical and prognostic value, as well as on management of this category of patients are provided. Comorbidities that are most prevalent in individuals with COPD are as follows: cardiovascular diseases, osteoporosis, gastroesophageal reflux disease, anemia, metabolic syndrome, depression and anxiety disorders.